INFLUENCE OF TECHNOLOGICAL PARAMETERS OF PORK PRODUCTION ON THE STRUCTURE OF PRODUCTION AND BREEDING PYRAMID - Замикула, В. В. (Scientific Progress & Innovations, 2014)
Pig industry always requires the increased attention as producers of pig products, Veterinary Service, and also state structures that monitor the situation and provide the government support to producers in the form of grants. Since the pig breeding is an area of ​​high-risk stock- breeding, the industry needs to develop and implement new technologies, tools and techniques that would help increase multiple pregnancy, the safety of the offspring, the intensity of growth and improving reproductive qualities of sows.